Incidence of Extended Spectrum Beta-Lactamase (ESBL) of Escherichia Coli Isolated from the Feces of Dairy Cattles in Blitar - Dameanti, Fidi Nur Aini Eka Puji; Amri, Indah Amalia; Roosdiana, Anna; Pratama, Alfaro Rikko; Izofani, Safira; Fahmiantika, Reza; Tedja, Dhaneswara; Sutrisno, Rahayu; Akramsyah, Muhammad Ali (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2023)
Antibiotic resistance (AMR) has caused a serious global threat to human health, animal health and food security. The antibiotic resistance problem, especially in Gram-negative bacteria, is increasingly widespread in various areas and has increased mortality, morbidity, and incidence. This study aims to determine the incidence of ESBL E. coli and the AMR and MDR properties of E.coli isolated from the feces of dairy cattles in Blitar, which have not been reported. This research was conducted from June to September 2022 with 60 samples of dairy cattle feces in Blitar. Samples were isolated and identified until confirmed that 55 (91.6%) samples were E. coli. All samples showed AMR character with 100% streptomycin, 87.27% chloramphenicol, 85.45% ampicillin, 72.73% cefotaxime, 40% tetracycline, 21.82% ciprofloxacin, and 14.55% sulfamethoxazole-trimethoprim. Forty-nine samples were MDR, with 10.9% resistant in three groups, 34.5% in four groups, 29.1% in five groups, 10.9% in six groups, and 3.6% in seven groups. MDR E. coli isolates were then confirmed for ESBL using the DDST test. The incidence of ESBL-producing E. coli from dairy cattle feces in Blitar was 40% (22 isolates). The results of this study can be a warning in the human health, animal health and food security.